Maximal lactate steady state does not correspond to a complete physiological steady state - Baron, B.; Dekerle, J.; Robin, S.; Neviere, R.; Dupont, L.; Matran, R.; Vanvelcenaher, J.; Robin, H.; Pelayo, P. (International Journal of Sports Medicine, 2003)
The purpose of this study was to verify whether the maximal lactate steady state (MLSS) corresponds to a physiological steady state. Eight male trained subjects performed a 30-min test on a cycle ergometer at a constant power corresponding to their own MLSS which had been previously determined. No significant variation was observed between the 10 (th) and the 30 (th) min for arterial lactate concentration, redox state, arterial oxygen pressure, arterial oxygen saturation, bicarbonates concentration, base excess, hematocrit, hemoglobin concentration, plasma volume, oxygen uptake, carbon dioxide output, gas exchange ratio, minute ventilation, ventilatory equivalents for oxygen and carbon dioxide, and arterial systolic blood pressure values. However, arterial carbon dioxide pressure and pH values were significantly different between the 10 (th) and the 30 (th) min (p < 0.01). Respiratory rate values and heart rate significantly increased (p < 0.01). These results indicate that MLSS does not correspond to a complete physiological steady state.